BREAST CANCER THERAPY: NEW TREATMENT METHODS FOR BREAST CANCER - Fayzullaeva Madina Bakhshillo kizi; Maxarova Moxinur Baxtiyor qizi; Sodiqova Nigoraxon Sodirjon qizi; Sindorova Jasmina Farxod qizi (TADQIQOTLAR, 2025)
Annotation: This article explores recent advancements in the treatment of breast cancer,  focusing  on  innovative  therapeutic  approaches  such  as  immunotherapy, targeted  therapy,  and  personalized  medicine.  The  study  reviews  clinical  trials  and scientific literature to highlight how these new methods improve patient outcomes, reduce side effects, and enhance survival rates. By comparing traditional treatments with modern techniques, the article provides insight into the evolving landscape of breast cancer management and outlines future directions in oncological care.